Komunikasi Antar Pribadi Siswa MAN 1 Medan - Khairuddin, Khairuddin (Lembaga Intelektual Muda (LIM) Maluku, 2024)
As communication people, it is important that we learn about the phenomena that occur in the process of communication change. The goal is to realize effective communication. Communication begins with an idea that exists in a person which is processed into a message that is conveyed and receives a response. This article uses a qualitative approach with the literature study method. This method is intended to examine various sources relevant to the focus of this research. The main sources of research data are scientific books and articles published in various scientific journals and indexed on the google scholar database. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that communication is very dominant in human life, especially interpersonal communication is very often done. Where the communication process occurs between individuals and usually occurs between two people directly. Interpersonal communication is communication between people face-to-face, which allows each participant to capture the reaction of others directly, either verbally or nonverbally. Interpersonal communication will be effective if it causes certain effects according to the intended purpose of the communicator. Based on the explanation above, it is very important that as a prospective guidance and counseling teacher/counselor understand interpersonal communication so that the counseling activities carried out can run well and efficiently